The Effect of Cage Type and Age on the Blood Profile of Broiler Chicken at the University Teaching Farm - Henni Vanda; Yolla Yolla; Wahyu Eka Sari; Muhammad Hambal (Jurnal Medika Veterinaria, 2022)
This study aimed to investigate the blood profile of broilers at the University Teaching Farm with different type of cages, namely stage, postal, and closed house cages. In this study, 36 blood samples from boilers aged 10 days and 25 days old were collected. Blood samples were collected from the jugular vein using a 3 mL syringe. The blood obtained was homogenized with an anticoagulant solution and analyzed using hematology Analyzer at Research Laboratory. The results showed that the highest number of erythrocytes of 10-day old broilers was found in stage cage, and at the age of 25 days, the highest erythrocytes was found in closed house cage. The highest number of leukocytes of broilers aged 10 days and 25 days were found in postal cage. The highest hemoglobin levels of broilers aged 10 days and 25 days old were detected in postal cage. The highest hematocrit value in 10-day-old broilers was found in closed house cage, while the highest hematocrit value of 25 days old broilers was in postal cage. It can be concluded that different type of cages and age have no impact on blood profile of broilers kept at the University Teaching Farm